Residential preferences and satisfaction among Iranian immigrant homeowners in Kuala Lumpur, Malaysia - Serish, Bahare Fallahi (2016)
The discussion on migration and mobility to other countries are attracting concern many in Iranian society. Numerous studies have investigated the underlying factors of residential satisfaction among nhabitants.Nonetheless, very few research have focused on the residential satisfaction, particularly among Iranian immigrants’ homeowners residing in another countries. Hence, the present study aimed to examine whether sociodemographic characteristics and residential preferences (i.e. housing preferences and neighborhood preferences) simultaneously predict residential satisfaction. Additionally, the study examined the role of housing preferences and neighborhood preferences as mediators between socio demographic characteristics and residential satisfaction. This study involved 235 Iranian immigrants’ homeowners in Kuala Lumpur, Malaysia which are selected at systematic random. Data were obtained from a cross-sectional survey and analyzed using “The Statistical Package for Social Sciences” (SPSS 21). Majority of the respondents (71.5%) reported moderate residential satisfaction. Using multiple regression analysis a significant model emerged (F (8, 226) =28.440, p≤.001, R=0.708, R Square=0 .502), where housing preferences and neighborhood preferences as well as household income significantly contributed to the prediction of residential satisfaction. Next, a series of 3-step multiple regression analyses and Sobel- test were conducted to examine the mediating effect of neighborhood preferences and housing preferences on the relationship between socio demographic factors and residential satisfaction. The analysis revealed that housing preferences significantly mediated the relationship between years of education, household size,and residential satisfaction. Also, findings showed that neighborhood preferences statistically mediate the relationships between years of education, household income, household size, and residential satisfaction. The results provided both theoretical and practical implications. Theoretically, findings supported and extended the Residential Satisfaction Model and Housing Adjustment Theory by adding residential preferences (housing preferences and neighborhood preferences) as a mediating factor. One of the important practical implication is that designers, planners should integrate preferences into housing and neighborhood as an important resource into their work for the development and maintenance of residential satisfaction of immigrants living in their host country.